Rubberwood Fiber Treatment by Laccase Enzyme and Its Application in Medium Density Fiberboard - Mohammed, Nasir; Othman, Sulaiman; Rokiah, Hashim; Hossain, Kaizar; Gupta, Arun; Mohd, Asim (Oriental Scientific Pub Co, 2015)
In this work physico-chemical properties of rubber wood fiber were analyzed after laccase treatment and evaluated the performance of medium density fiberboard (MDF) fabricated from the treated fiber. In a single parameter study, two different times i.e. 60 min and 120 min of laccase treatment were applied at constant temperature, enzyme concentration and pH. After the pulp treatment, fibers were sieved out and transferred in to autoclave at 121 °C for 15 min to stop further enzyme reaction. Treated fiber was dried in electric oven drier at 80-90°C for 24 hr to dry up the fiber until constant moisture content. Crystallinity index of the fiber was measured by X-ray diffraction method and it was observed maximum up to 14% higher compared to untreated fiber. The treated fiber was further analyzed for FE-SEM, TGA and compared with untreated fiber in order to evaluate its properties. Fiber treated with enzyme exhibited superiority in fiber surface structure and thermal degradation over untreated fibers. The MDF prepared from improved crystalline fiber showed improved physical and mechanical properties as compared to the MDF from untreated fiber.